Increased Serum NSE and S100B Indicate Neuronal and Glial Alterations in Subjects Under 71 Years With Mild Neurocognitive Disorder/Mild Cognitive Impairment - Polyakova, Maryna; Mueller, Karsten; Arelin, Katrin; Lampe, Leonie; Rodriguez, Francisca S.; Luck, Tobias; Kratzsch, Jürgen; Hoffmann, Karl-Titus; Riedel-Heller, Steffi; Villringer, Arno; Schoenknecht, Peter; Schroeter, Matthias L. (Frontiers in Cellular Neuroscience, 2022)
ABSTRACT Mild cognitive impairment (MCI) is considered a pre-stage of different dementia syndromes. Despite refined by DSM-5 diagnostic criteria and a new term for MCI – “mild neurocognitive disorder” (mild NCD) – this diagnosis is still based on clinical criteria. To link mild NCD to the underlying pathophysiology we assessed the degree of white matter hyperintensities (WMH) in the brain and peripheral biomarkers for neuronal integrity (neuron-specific enolase, NSE), plasticity (brain-derived neurotrophic factor, BDNF), and glial function (S100B) in 158 community-dwelling subjects with mild NCD and 82 healthy controls. All participants (63 – 79 years old) were selected from the Leipzig-population-based study of adults (LIFE). Serum S100B levels were increased in mild NCD in comparison to controls (p=0.007). Serum NSE levels were also increased, but remained non-significant after Bonferroni-Holm correction (p=0.04). Furthermore, age by group interaction was significant for S100B. In an age-stratified sub-analysis, NSE and S100B were higher in younger subjects with mild NCD below 71 years of age. Some effects were inconsistent after controlling for potentially confounding factors. The discriminatory power of the two biomarkers NSE and S100B was insufficient to establish a pathologic threshold for mild NCD. In subjects with mild NCD, WMH load correlated with serum NSE levels (r=0.20, p=0.01), independently from age. Our findings might indicate the presence of neuronal (NSE) and glial (S100B) injury in mild NCD. Future studies need to investigate whether younger subjects with mild NCD with increased biomarker levels are at risk for development of major NCD.